GAMBARAN PENGETAHUAN IBU HAMIL DAN DUKUNGAN SUAMI TERHADAP KUNJUNGAN ANTENATAL CARE (ANC) DI DESA SALO TIMUR WILAYAH KERJA PUSKESMAS SALO TAHUN 2020 - Lestari, Rizki Rahmawati; Isnaeni, Lira Mufti Azzahri; Z.R, Zurrahmi (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
A good ANC as early as possible can improve the quality of pregnant women and prevent maternal and infant mortality. The purpose of this study was to describe the knowledge of pregnant women and husband's support about Antenatal Care (ANC) in Salo Timur Village, Salo District in 2020. The type of research used is quantitative with a descriptive design. The population in this study were all pregnant women with gestational age> 36 weeks who were in the Salo Health Center working area during the period in October 2020, as many as 49 people with total sampling technique. The data collection tool used a questionnaire. Data analysis in this study used univariate analysis. The results showed that most respondents had less knowledge about ANC, did not get support from their husbands and the majority of respondents did not complete ANC visits. It is hoped that respondents will be aware of the importance of ANC visits during pregnancy so that they can find out about any diseases during pregnancy.